2011
DOI: 10.1248/yakushi.131.775
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Therapeutic Effects of Hybrid Liposomes on the Alzheimer's Disease in Vitro

Abstract: Accumulation of b amyloid (Ab) peptides to nerve cells should be associated with the onset of Alzheimer's disease (AD). We prepared hybrid liposomes (HL) composed of 90 mol% phospholipids having various charged head groups (cationic L-a-dimyristoyltrimethyl ammonium propane (DMTAP), anionic L-a-dimyristoylphosphatidylserine (DMPS) or zwitterionic L-a-dimyristoylphosphatidylcholine (DMPC)) and 10 mol% polyoxyethylene(23) dodecyl ether (C 12 (EO) 23 )), and investigated the inhibitory eŠects of HL on the accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In the first study, they investigated the inhibitory effects of hybrid liposomes on the accumulation of amyloid beta 1-40 for SH-SY5Y cells. They prepared liposomes composed by phospholipids having various charged head groups (cationic L-alpha-dimyristoyltrimethyl ammonium propane (DMTAP), anionic L-alpha-dimyristoylphosphatidylserine (DMPS), or zwitterionic L-alpha-dimyristoylphosphatidylcholine (DMPC)) and polyoxyethylene(23) dodecyl ether (C(12)(EO)(23)), and found that the cytotoxicity of amyloid-beta (1-42) peptides on the SH-SY5Y cells decreased after the treatment with this formulation of liposomes [82]. In the other in vitro study, they applied unilamellar liposomes in HEK-APP cells, providing protection from oxidation and effective incorporation of omega-3 fatty acid docosahexaenoic acid (DHA) into cell membranes comparing with HEK293 control cells.…”
Section: Liposomes As Neuropharmacological Agentsmentioning
confidence: 99%
“…In the first study, they investigated the inhibitory effects of hybrid liposomes on the accumulation of amyloid beta 1-40 for SH-SY5Y cells. They prepared liposomes composed by phospholipids having various charged head groups (cationic L-alpha-dimyristoyltrimethyl ammonium propane (DMTAP), anionic L-alpha-dimyristoylphosphatidylserine (DMPS), or zwitterionic L-alpha-dimyristoylphosphatidylcholine (DMPC)) and polyoxyethylene(23) dodecyl ether (C(12)(EO)(23)), and found that the cytotoxicity of amyloid-beta (1-42) peptides on the SH-SY5Y cells decreased after the treatment with this formulation of liposomes [82]. In the other in vitro study, they applied unilamellar liposomes in HEK-APP cells, providing protection from oxidation and effective incorporation of omega-3 fatty acid docosahexaenoic acid (DHA) into cell membranes comparing with HEK293 control cells.…”
Section: Liposomes As Neuropharmacological Agentsmentioning
confidence: 99%
“…If, during the last century researchers attempted to use cells as simple drug carriers or containers, as well as to improve encapsulation procedure for different drugs, then today DDS has developed more fascinating, complex, and interactive systems. [26][27][28][29][30][31][32][33][34][35][36] The main requirements for DDS include: (1) The drug should influence the pathological foci solely and must not have any side or toxic effects; (2) drug properties should remain intact on the way to the drug's destination, with mechanisms in place to control for over-dosage; and (3) there should be effective target reliability, which ensures that drugs reach their final settings. DDS can be conventional and can be target organ or tissue specific.…”
Section: Targeted Ddsmentioning
confidence: 99%